Design of Tunable Equalizers Using Multilayered Half Mode Substrate Integrated Waveguide Structures Added Absorbing Pillars - Shuxing Wang; Yongfei Wang; Dewei Zhang; Yi Zhang; Dongfang Zhou (Advances in Materials Science and Engineering)
An equalizer based on multilayered half mode substrate integrated waveguide (HMSIW) structures with high Q-factor, low loss, and compact size is proposed for the first time. Resonant cavities distributing in the upper substrate and the bottom substrate, with the middle substrate layer which works as the transmission line together, constitute a multilayer structure. The design method and theoretical analysis are summarized first. The mode analysis, simulated results, and measured results are all provided. The measured results show a good performance and are in agreement with the simulated results, and the maximum attenuation slope reaches −16 dB over 12.5 GHz~14.5 GHz. With the use of absorbing pillars, the attenuation and Q value can be tuned more easily than the other planar equalizers. Compared with the SIW equalizer, the size of this structure reduces by 50%. Furthermore, this structure is suitable for the miniaturization development of equalizers.